ANALYSE LES PERFORMANCES D’UN SYSTÈME DS-OCDMA EN UTILISANT LES CODES OPTIQUE ORTHOGONAUX (OOC) - M. Bouregaa; M. Chikh-Bled; A. Ikhlef (European Scientific Journal, ESJ, 2013)
In a DS-OCDMA system, the MAI is one of the major limitations due to the unipolarity of the codes used. To mitigate the MAI, several techniques are developed for receptions eliminate the contribution of unwanted users. In this work, we studied the characteristics of correlations OOC codes, and we presented three structures of receptors that are well placed to estimate the information bits. For this, we have developed the theoretical BER expressions error probability.